Was the knowledge of the second language or the age difference the determining factor? - Sullivan, Kirk P. H.; Kügler, Frank (International Journal of Speech, Language and the Law, 2001)
In a legal setting a witness may be asked to recognize a suspect based on a voice sample alone. Previous research has shown that knowledge of a language has an effect on an individual’s ability to identify speakers. Recent research using a set of voice line-ups has demonstrated that there was no unambiguous improvement in the ability to recognize and identify speakers during the four years of BA (hons) Swedish study by British university students. This research, however, used a younger group of high school students as the control group of listeners with no knowledge of Swedish. This paper investigates, using the same methodology, whether the difference in this earlier study, between the control group and the three university groups was due to knowledge of Swedish or age. The results of this study show that knowledge of Swedish was the factor which resulted in the difference between the control group and the three experimental groups in the earlier study.